Analysis on thermal hydraulic performance of the elliptical tube in the finned-tube heat exchanger by new method. (May 2019) - Wang, Qiang; Qian, Zuoqin; Cheng, Junlin; Huang, Weilong; Ren, Jie
Highlights: The theory of Karman vortex street was adopted to explain the reason of weak region formation. Two tube configurations of which the section was semicircular and semielliptical were discussed in this paper. The velocity vector, the flow streamline and the temperature contour of the modified configurations were displayed. Abstract: The main objectives were to develop a method for designing an effective finned heat exchanger through changing the configuration to ensure the tubes be streamlined shape. Kinds of inserts including, vortex generator, louver fin, and serrated fin in the heat transfer was used to increase the effect of thermal performance, but also was harmful to the flow characteristics. Consequently, the comprehensive performance was obviously lower than the heat exchangers with no inserts. In order to solve this problem, streamlined tube configuration was adopted in this paper to search a new method to enhance the comprehensive performance by reducing the Karman vortex street effect. Two modified configurations of tube were investigated in this paper. The modified configurations were both made of semicircular tube and semielliptical tube. The simulation was validated by Wang's experiment and Arafat's simulation. The numerical data were presented at Reynolds number in the range between 1300 and 2000. Based on the numerical results, the effect of elliptical axis ratio on the thermal hydraulic performance was discussed. The results showed that the comprehensive performance of the modified configurations was greater than that of the circular tube. In addition, the velocity vector, flow streamline and temperature contour of the configurations were displayed. The Karman vortex street effect was adopted to explain the reason of wake region formation. It can be concluded that long and thin section of heat transfer tube, which was coincident with streamlined design, was beneficial to improve the comprehension performance of the heat exchanger.